Studi Interferometer Fabry-Perot Untuk Pengukuran Panjang Gelombang Cahaya - Satoto, Dwi; Sugito, Heri; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
In this experiment, an interferometer Fabry-Perot method has been used to measure wavelength of diode laser. The first step is to calibrate the micrometer displacement using He-Ne laser in order to measure the diode and He-Ne wavelength. By shifting movable mirror, the transition of interference fringe in counted against the displacement of movable mirror. For the result of measurement, it is obtained for the wavelength of the red diode laser of, and green diode laser of. Â  Key word: Interferometer Fabry Perot, multiple beam interference.